Quality of Investigative Journalism in Lithuania: Analysis of Research by Public Broadcaster LRT and News Portal 15min - Majūtė, Vaidota (Žurnalistikos tyrimai, 2024)
The article formulates criteria for the quality of investigative journalism based on the literature analysis, which are used to assess and compare the quality of investigations conducted in 2022 and 2023 by two traditional Lithuanian media outlets – the public broadcaster LRT and the commercial news portal 15min. The author reveals a journalistic view of the quality of research, showing similarities and differences in approaches; having assessed five studies in both media outlets and the responses of journalists, she emphasizes that some investigations lack an objective balance of sources, and the investigations do not always meet high standards and methods.
Keywords: quality of journalism; investigative journalism; quality criteria for investigative journalism; quality of journalistic investigations